The Meaning of “Ideal Dating” in Gender Role Construction: A Phenomenological Study of Student Experiences in Surabaya - Diandra Wahzu Hairina Putri; Ahmad Ridwan; Refti Handini Listyani; M. Jacky (University of Muhammadiyah Malang, 2026)
This study explores the meaning of “ideal dating” and gender role constructions in the experiences of students in Surabaya. Dating as a social phenomenon among students is a complex space where various values, norms, and societal expectations meet and negotiate. Using a qualitative approach with descriptive phenomenology, this study involved five students in Surabaya through purposive sampling and snowball sampling. Data were collected through semi-structured in-depth interviews and analyzed using qualitative descriptive methods. The results show that “ideal dating” for Surabaya students is a dynamic social construct that emphasizes open communication, mutual emotional support, mutual understanding, and a commitment to growing together. Four main pillars were identified: communication and openness, mutual understanding and ego management, support as a manifestation of love, and role balance. Masculinity is still associated with financial responsibility and decision-making, while femininity is linked to emotional sensitivity and a supportive role. However, there is a strong tendency toward egalitarian relationship patterns, reflected in respondents' consistent rejection of the view that “men's love must be greater.” Social pressures such as academic demands, organizational commitments, and the influence of social media are negotiated through intense communication, ego management skills, and emotional adaptation. The study concludes that the meaning of ideal dating is shaped by the interaction between traditional values, modern demands, and evolving subjective experiences. This suggests that ideal dating is not fixed, but continuously negotiated by students within their social and personal contexts